2010
DOI: 10.1016/j.ijid.2010.02.1992
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of isolated hepatitis B core antibody among injection drug users in Central Province of Iran

Abstract: ing liver cirrhosis and/or liver cancer. Occult hepatitis C virus (OCV) infection is characterized by presence of HCV infection with undetectable hepatitis C antibodies or/and RNA in serum. Scanty information is available about the etiology of viral chronic liver diseases in the United Arab Emirates (UAE). Therefore a study was carried out for detecting and genotyping of HCV & OCV in patients with chronic liver disease (CLD) in UAE.Methods: A total of 142 serum samples from CLD patients and 139 healthy individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…They included 153 IDUs of Arak, central province of Iran; in their study, they found that about 7.84% of subjects have isolated anti-HBc. [ 19 ]…”
Section: Discussionmentioning
confidence: 99%
“…They included 153 IDUs of Arak, central province of Iran; in their study, they found that about 7.84% of subjects have isolated anti-HBc. [ 19 ]…”
Section: Discussionmentioning
confidence: 99%